Obesity and metabolic syndrome in COPD: Is exercise the answer?. (May 2018) - James, Benjamin D; Jones, Amy V; Trethewey, Ruth E; Evans, Rachael A
Approximately half of all patients with chronic obstructive pulmonary disease (COPD) attending pulmonary rehabilitation (PR) programmes are overweight or obese which negatively impacts upon dyspnoea and exercise tolerance particularly when walking. Within the obese population (without COPD), the observed heterogeneity in prognosis is in part explained by the variability in the risk of developing cardiovascular disease or diabetes (cardiometabolic risk) leading to the description of metabolic syndrome. In obesity alone, high-intensity aerobic training can support healthy weight loss and improve the constituent components of metabolic syndrome. Those with COPD, obesity and/or metabolic syndrome undergoing PR appear to do as well in traditional outcomes as their normal-weight metabolically healthy peers in terms of improvement of symptoms, health-related quality of life and exercise performance, and should therefore not be excluded. To broaden the benefit of PR, for this complex population, we should learn from the extensive literature examining the effects of exercise in obesity and metabolic syndrome discussed in this review and optimize the exercise strategy to improve these co-morbid conditions. Standard PR outcomes could be expanded to include cardiometabolic risk reduction to lower future morbidity and mortality; to this end exercise may well be the answer.